Variation in avian morphology along a short tropical elevational gradient. (19th May 2022) - Lele, Abhimanyu; Garrod, Holly M.; Ferguson, Euan; Azahara Prieto Gil, Carmen; Ellis, Mike
Abstract: Patterns across species of intraspecific phenotypic variation with environment can shed light on the underlying drivers of adaptive evolution. Phenotypic variation within a species along tropical elevational gradients is of particular interest because species with narrow elevational ranges may still experience considerably varied environmental conditions. Here, we examine morphological variation in 27 tropical bird species, spanning 11 families and 3 orders, across a 675 m elevational gradient in Western Ecuador. We analyzed a data set of six morphological variables in 3263 individual birds using multivariate analyses of variance (MANOVAs) and canonical correlation analyses (CCAs). We found that morphology varies significantly with elevation in 8 species, and that spatial segregation by age or sex was apparently not responsible for this result. The phenotypic traits that varied with elevation varied strongly by species. To the best of our knowledge, morphological variation over equally short elevational and horizontal distances across a diverse suite of vertebrate species has not previously been demonstrated. Abstract in Spanish is available with online material. Abstract : Patterns across species of intraspecific phenotypic variation with environment can shed light on the underlying drivers of adaptive evolution. Here, we examine morphological variation in 27 tropical bird species along a 675 m elevational gradient in Western Ecuador using multivariate analyses. We found that morphology varies significantly with elevation in 8 species, and that spatial segregation by age or sex was apparently not responsible for this result.